Optimality Criteria in Rotation - Rustagi, Krishna P. (Indian Forester, 1975)
The current forest productivity in India is rather low. It should be possible to substantially increase current as well as future productivity by adopting rationally determined rotations based on output and/or financial criteria. This paper emphasizes this approach, and outlines criteria which could be used in the evaluation of existing and proposed rotations.